2020
DOI: 10.1186/s11689-020-09317-2
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of neural progenitor cells derived from Lowe syndrome induced pluripotent stem cells: identification of candidate genes for the neurodevelopmental and eye manifestations

Abstract: Background Lowe syndrome (LS) is caused by loss-of-function mutations in the X-linked gene OCRL, which codes for an inositol polyphosphate 5-phosphatase that plays a key role in endosome recycling, clathrin-coated pit formation, and actin polymerization. It is characterized by congenital cataracts, intellectual and developmental disability, and renal proximal tubular dysfunction. Patients are also at high risk for developing glaucoma and seizures. We recently developed induced pluripotent stem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 127 publications
0
10
0
Order By: Relevance
“…To identify the candidate genes from the DEGs obtained via RNA-seq analysis that may be associated with the pathology of posterior congenital cataract, we next analysed the DEGs using the database resource of iSyTE2.0 [ 5 ], which represented the gene expression and lens enrichment data during the normal lens development. Previous studies have suggested that the database iSyTE could be a cataract gene prioritization resource [ 10 ] and 95% of known genes associated with cataract or lens defects are lens-enriched at one or more key embryonic stages [ 6 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To identify the candidate genes from the DEGs obtained via RNA-seq analysis that may be associated with the pathology of posterior congenital cataract, we next analysed the DEGs using the database resource of iSyTE2.0 [ 5 ], which represented the gene expression and lens enrichment data during the normal lens development. Previous studies have suggested that the database iSyTE could be a cataract gene prioritization resource [ 10 ] and 95% of known genes associated with cataract or lens defects are lens-enriched at one or more key embryonic stages [ 6 ].…”
Section: Resultsmentioning
confidence: 99%
“…The gene-specific primers for RT-qPCR are shown in Table 1 . The results were analysed using the 2 −ΔΔCt method as described previously [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…In Cluster #5, the major citing document is written by Al-Dewik et al [ 132 ] and has a coverage of 20 documents and a GCS of 5. As the term “Genomic Architectured” implies, many studies in this cluster make use of big data, such as genome-wide associations or transcriptome analyses, to uncover the genetic bases of ASD [ 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 ]. The top 10 citing papers of Cluster #5 are seen in Table 9 .…”
Section: Discussionmentioning
confidence: 99%
“…These studies were complemented by biochemical and cell biological assays to assess the mutational impact on protein function and availability ( De Leo et al, 2016 ; Ramadesikan et al, 2021 ). Furthermore, models were prepared by various methods to gain mechanistic insight into LS such as KO/morpholino zebrafish lines ( Coon et al, 2012 ; Ramirez et al, 2012 ; Gliozzi et al, 2020 ), humanized mouse models ( Bothwell et al, 2011 ), Ocrl1-deficient cells by CRISPR ( Madhivanan et al, 2020 ) along with stable lines expressing specific variants ( Ramadesikan et al, 2021 ), and patient-derived iPSCs ( Barnes et al, 2018 ; Hsieh et al, 2018 ; Liu et al, 2020 ; Akhtar et al, 2022 ). Taken together, LS research has greatly benefitted from the assimilation of a variety of techniques and is rapidly moving towards understanding LS in a patient mutation-specific manner to better guide the design novel therapeutic approaches.…”
Section: Advances Towards the Use Of An Integrated And Updated Multid...mentioning
confidence: 99%